EFFECTIVENESS OF USING EXTENSION MEDIA IN INFORMATION DIFFUSION OF SUSTAINABLE FOOD COURTS AS AN EFFORT TO ANTICIPATE THE FOOD CRISIS: EFEKTIVITAS PENGGUNAAN MEDIA PENYULUHAN DALAM DIFUSI INFORMASI PEKARANGAN PANGAN LESTARI (P2L) SEBAGAI UPAYA ANTISIPASI KRISIS PANGAN - Dela Fitria Nurdiantini; Muhammad Ravi Al qifary (Politeknik Pembangunan Pertanian Bogor, 2022)
The Covid-19 pandemic outbreak has an impact on the global food crisis which threatens countries in the world. In Indonesia, food availability is important to maintain national economic stability, so that food security needs to be increased by realizing food sovereignty and self- sufficiency (food resilience). Agricultural extension as the spearhead of agricultural development has an important role in disseminating information to farmers as an effort to prevent food crises in Indonesia. The success of extension activities will not be separated from the influence of extension media. In today's digital era, extension media has developed a lot. The effectiveness of the use of extension media in accelerating the dissemination of information needs to be known to be used as a recommendation for agricultural extension workers in choosing the right media.This study aims to determine the level of effectiveness of extension media in the diffusion of P2L information, so that it can be identified which types of media are effective in carrying out extension activities. This research uses descriptive analysis method and data processing using multiple linear regression. The research variables used were printed (X1), projected (X2), and audio-visual (X3) extension media, as well as effectiveness (Y1).The results showed that the effect of agricultural extension media on the level of effectiveness of agricultural extension in P2L information diffusion was 61.3%. Variables that have a one-way contribution are printed extension media (X1) of 0.043 and audio-visual (X3) of 1.3. Meanwhile, the variable that has a non- unidirectional contribution is the projected extension media (X2) of -0.163. Referring to the results obtained, it can be concluded that the most effective agricultural extension media in P2L information diffusion is audio-visual. Thus extension workers should optimize the use of audio- visual media in extension activities.